Analisis Korelasi Akurasi, Ketepatan Waktu Dan Relevansi Informasi Terhadap Kepuasan Pemakai Sistem Informasi PT. Perisai Husada - Dudi Pratomo; Willy S. Yuliandhari (Jurnal Manajemen dan Bisnis Indonesia, 2014)
The use of information systems that needed by users, must be accurate, timeliness and relevant. Accurate reflect the information must be clearly presented and not biased or miss-understanding, timeliness means that information is available when needed, relevant information is useful for users.The aim of this research is to analize the correlation between accurate, timeliness and relevant for the satisfaction of user information system, which partially and simultainly. The research method is descriptive verificative, case study at PT. Perisai Husada, with the number of respondens are 30 workers who users of the information system. The results of this recearch prove that accurate information and relevant information have a strong corelation to user satisfaction but timeliness information have a low correlation. Key words: Accurate, timeliness, relevant information, user satisfaction of information system